Self-Concept among Students Displaced For Middle School - Jaafar, Ihsan Talib (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to (unveil the self-concept of the displaced students for the intermediate stage), and the current research community included fourth-grade middle school students in Karbala and those who are studying for the academic year 2014-2015. (40) Students were selected as a sample for the research, and followed the descriptive approach in the current research, the research included two tools, as follows First The researcher adopted the scale (Al-Mostafawi 2005) of the concept of self-consisting of (48) paragraphs, and then the apparent honesty of the scale was achieved. Second Fee Analysis Form A tool was built up of (6) fields, (1㫠) a major property, and (51) a secondary property, and the validity of the tool was verified by presenting it to a group of experts and specialists, while stability was used by external analysts. As for the subject of the drawing, a fee (free subject) was agreed upon, as the total of the fees analyzed reached (40) fees. In order to reach the results of the research, I used the appropriate statistical equations for that. After the results were presented and discussed, the researcher reached a number of recommendations, including 1-Activating the role of civil society institutions and organizations, in coordination with the general directorates of education, to provide material and moral support and psychological rehabilitation for the displaced students, and to raise part of their suffering that was caused to them as a result of the events they experienced 2.Activating the art education lesson inside the educational institution, especially in schools for displaced students, and being the only lesson that has the ability to reveal the status of students and their suffering, and the unique lesson from the rest of the lessons, which is a mirror that reflects the values ​ ​ of students and their attitudes towards various things and situations, and those surrounding them within the family and school And the general environment.